A study on the environment protection and the effect of solid waste material dumping on environment - Nashine, Reena (Recent Research in Science and Technology, 2013)
<span style="font-size: 10.0pt; line-height: 115%; font-family: "Arial Narrow","sans-serif"; mso-fareast-font-family: BatangChe; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 1.0pt; mso-fareast-language: KO; mso-bidi-font-weight: bold;">The impact of rapid industrialization around the globe and unsafe waste management practices have become increasingly significant within the last two decades as the disclosed number of un-engineered facilities and contaminated sites steadily grow and the anticipated remediation costs increase. A new service sector is emerging across the world in waste containment, soil remediation and environmental restoration. The need to accomplish the tasks given in environmental restoration and waste management places a new responsibility on the services of the environmental engineer. It requires collaboration between geotechnical and environmental engineers. This paper deals with the detailed study of the impact of solid waste dumping on the Geo-Environment. The case study done helps to actual visualization of the effects of the same!